Venturing into the Wilderness. Preparing for Wild Cards in the Civil Aircraft and Asset-Management Industries - Mendonça, S. (Long Range Planning, 2009)
We consider ways in which radically uncertain and disruptive events may be introduced into corporate decision making structures. As a foresight concept, ‘‘wild cards’’ refer to trend-breaking/trend-creating events that are very hard or even impossible to anticipate, but that should nonetheless be expected in complex and fast-evolving environments. The discussion is grounded in the experience obtained in two strategic foresight projects carried out in two industries d civil aviation and investment banking. The unique strength of these cases is that they constitute concrete and rare examples of disclosed business foresight studies that, from the start, included an explicit wild card element. Most interestingly, both of these cases are analytically linked to the September 11 event, a severe instance of a wild card. A key rationale for wild card-friendly foresight research is that it is a source of critical inputs for the generation of robust decisions precisely when the organisation is under pressure from unexpected dramatic strategic discontinuities.